2015
DOI: 10.1155/2015/276029
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amniotic LPS Induced Region-Specific Changes in Presynaptic Bouton Densities in the Ovine Fetal Brain

Abstract: Rationale. Chorioamnionitis has been associated with increased risk for fetal brain damage. Although, it is now accepted that synaptic dysfunction might be responsible for functional deficits, synaptic densities/numbers after a fetal inflammatory challenge have not been studied in different regions yet. Therefore, we tested in this study the hypothesis that LPS-induced chorioamnionitis caused profound changes in synaptic densities in different regions of the fetal sheep brain. Material and Methods. Chorioamnio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…As IUGR neurodevelopment is thought to be delayed due to reduced nutrients during a critical phase of cerebral development (2628), the present result suggest that IUGR leads to transient delay in synaptogenesis in the cortex in P7 restricted rats. Similarly in sheep (29), impaired fetal environment was induced by an intra-amniotic lipopolysaccharide pro-inflammatory environment and cerebral synaptophysin expression was reported to be decreased in motor, somatosensory and entorhinal cortices causing reduction in density of presynaptical boutons.…”
Section: Discussionmentioning
confidence: 99%
“…As IUGR neurodevelopment is thought to be delayed due to reduced nutrients during a critical phase of cerebral development (2628), the present result suggest that IUGR leads to transient delay in synaptogenesis in the cortex in P7 restricted rats. Similarly in sheep (29), impaired fetal environment was induced by an intra-amniotic lipopolysaccharide pro-inflammatory environment and cerebral synaptophysin expression was reported to be decreased in motor, somatosensory and entorhinal cortices causing reduction in density of presynaptical boutons.…”
Section: Discussionmentioning
confidence: 99%
“…CA is associated with 40-70% of preterm births (Jain et al, 2021) and leads to cerebral lesions and neurodevelopmental delay (Adams-Chapman & Stoll, 2006); however, the links are not clear and may depend on the time, duration and type of perinatal in ammation. CA may induce lesions in white matter, such as altered vascular microstructure and periventricular hemorrhage, as well as lesions in grey matter, such as increased neuronal apoptosis, abnormal neuronal circuit formation and cognitive impairments (Versland et al, 2006;Nasef et al, 2013;Strackx et al, 2015;Anblagan et al, 2016). Recent data also suggested that neuropsychiatric disorders, such as autism spectrum disorder and schizophrenia, might have a neurodevelopmental origin and be linked to feto-maternal in ammation (Pinelli & Zwaigenbaum, 2008;Hagberg et al, 2015;Estes & McAllister, 2016;Thorell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data also suggested that neuropsychiatric disorders, such as autism spectrum disorder and schizophrenia, might have a neurodevelopmental origin and be linked to feto-maternal in ammation (Pinelli & Zwaigenbaum, 2008;Hagberg et al, 2015;Estes & McAllister, 2016;Thorell et al, 2020). CA-related brain lesions may be mediated in spatiotemporal ways by several mechanisms, including transport of cytotoxic molecules across the blood-brain barrier (BBB), transient activation of microglia accompanied by release of proin ammatory cytokines and reactive oxygen species, arrest of preoligodendrocyte maturation followed by hypomyelination, reduced synaptic density, impaired neurogenesis and cell death (Burd et al, 2012;Back & Rosenberg, 2014;Strackx et al, 2015;Penn et al, 2016;Gussenhoven et al, 2018). In particular, the hippocampus, a brain region centrally involved in memory and cognitive processes, was shown to be affected in various preclinical models of CA (Gavilanes et al, 2009;Gussenhoven et al, 2018), and it has a smaller volume in preterm infants exposed to CA (Hat eld et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CA is associated with 40-70% of preterm births (Jain et al, 2021) and leads to cerebral lesions and neurodevelopmental delay (Adams-Chapman & Stoll, 2006); however, the links are not clear and may depend on the time, duration and type of perinatal in ammation. CA may induce lesions in white matter, such as altered vascular microstructure and periventricular hemorrhage, as well as lesions in grey matter, such as increased neuronal apoptosis, abnormal neuronal circuit formation and cognitive impairments (Versland et al, 2006;Nasef et al, 2013;Strackx et al, 2015;Anblagan et al, 2016). Recent data also suggested that neuropsychiatric disorders, such as autism spectrum disorder and schizophrenia, might have a neurodevelopmental origin and be linked to feto-maternal in ammation (Pinelli & Zwaigenbaum, 2008;Hagberg et al, 2015;Estes & McAllister, 2016;Thorell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%